Determinations of the factor that affecting the housing price in Asia Pacific 2008-2017 (10 YEARS) / Muhamad Syafiq Abdul Rahman - Abdul Rahman, Muhamad Syafiq (2020)
This research paper was conducted to measure the relationship between house price, real interest rate, inflation rate, population growth, gross domestic product (GDP) per capita in 13 Asia Pacific Countries which include Bangladesh, China, India, Indonesia, Israel, Japan, Jordan, Korea, Malaysia, Pakistan, Philippines, Singapore and Thailand. However, there is only a few researchers had been done regarding in Asia Pacific countries. This paper also examines empirically whether the increasing or decreasing trend in 13 Asia Pacific countries. This study employed panel data ranging from year 2008 until 2017 which consists of eleven (10) years. We use STATA 14 that encompass descriptive analysis, correlation analysis, regression analysis and Multi-co linearity test. Our findings indicate that one independent variable which is GDP have significant relationship with house price but may not necessarily be influenced by GDP in Asia Pacific countries. However, another three independent variables which are interest rate, inflation rate and population did not have significant relationship with house price. This paper can serve as a guide for the investors, buyers, speculators and future researchers to know which factors to account for in housing investment decision.